How is Students’ Creative Thinking Skills? An Ethnoscience Learning Implementation - Khoiri, Ahmad; Nulngafan, Nulngafan; Sunarno, Widha; Sajidan, Sajidan (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2019)
The objectives of this research is to know the characteristics of ethnoscience learning in developing creativity and testing its effect on students' creativity. This type of research is a Quasi-experimental one-group pretest-posttest design. A total of 31-third year students from Physics Education study programs were chosen as the sample of the research through a purposive sampling technique. The data collection methods used were Torrance Test Creative Thinking, creativity questionnaires, in-depth interviews, and documentation. T-test with T-value test by LISREL 8.8 Second-order CFA application was used to analyze the data. The results showed that the ethnographic science learning model is a strategy for creating and designing a learning environment that integrates community culture through environmental studies. Based on the t-test, the indicator of creativity is 4.47, flexibility is 5.22, originality is 4.88, elaboration is 5.96, and redefinition is 6.24, with Ttable of 1,97. It means that ethnoscience learning is effective in increasing student creativity. It is recommended to reconstruct the original science into scientific science to preserve the culture of society which is a challenge in the era of industrial revolution 4.0.